Concept and essence of the educational service as a legal category - Shaimukhanova, Zh.T.; Dussipov, Ye.Sh.; Njiki, Michel Remi (Bulletin of the Karaganda University “Law Series”, 2020)
The sphere of educational services has always been of particular importance. Educational services is the leading activity of higher education institutions. The provision of educational services is regulated by the Civil code of the Republic of Kazakhstan.This scientific article briefly discusses the provision of educational services, defines the legal concept and features of the provision of educational services. The essence of the educational service is revealed as the activity of training and education, which consists skills aimed at developing the spiritual state of the learner's personality. The authors highlighted the features of the provision of educational services as a subject of civil legal relations (unsuitability for exploitation; variability of quality; lack of guarantees; complexity; inseparability from the source).The conclusion is made on the basis of existing norms, about the need to develop additional legal mechanisms for protecting the rights of consumers of services in the field of education.